2012
DOI: 10.1113/expphysiol.2011.062257
|View full text |Cite
|
Sign up to set email alerts
|

Different patterns of pulmonary vascular disease induced by type 1 diabetes and moderate hypoxia in rats

Abstract: Although type 1 and type 2 diabetes are strongly associated with systemic cardiovascular morbidity, the relationship with pulmonary vascular disease had been almost disregarded until recent epidemiological data revealed that diabetes might be a risk factor for pulmonary hypertension. Recent experimental studies suggest that diabetes induces changes in lung function insufficient to elevate pulmonary pressure. The aim of this study was to assess the effects of diabetes on the sensitivity to other risk factors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 44 publications
(58 reference statements)
3
30
1
Order By: Relevance
“…; Moral‐Sanz et al . ); however, there is a slightly higher sensitivity to hypoxia in T1D rats than in control rats (Moral‐Sanz et al . ).…”
Section: Vascular Function In Hyperglycaemiamentioning
confidence: 99%
See 1 more Smart Citation
“…; Moral‐Sanz et al . ); however, there is a slightly higher sensitivity to hypoxia in T1D rats than in control rats (Moral‐Sanz et al . ).…”
Section: Vascular Function In Hyperglycaemiamentioning
confidence: 99%
“…); however, there is a slightly higher sensitivity to hypoxia in T1D rats than in control rats (Moral‐Sanz et al . ). We demonstrated that RVSP was slightly, but significantly, increased in T2D mice (both inducible T2D and KK mice) compared to the controls.…”
Section: Vascular Function In Hyperglycaemiamentioning
confidence: 99%
“…Isolated pulmonary arteries of insulin resistant rats show diminished acetylcholine-mediated nitric oxide release, as well as upregulation of NADPH oxidase, 5-HT, and cycloxygenase-2 proteins [7577]. Interestingly, in animal models, insulin resistance coupled with moderate hypoxia results in PH and right ventricular hypertrophy while neither insulin resistance nor hypoxemia alone induces PH or right ventricular hypertrophy [78]. Treatment with insulin sensitizing agents can reverse PH and attenuate pulmonary artery remodeling in insulin-resistant rodents [79, 80].…”
Section: Specific Pathophysiologic Mechanismsmentioning
confidence: 99%
“…Diabetes can potentially exacerbate inflammation, increase the production of proinflammatory cytokines, and enhance parenchymal infiltration of neutrophils and macrophages in rat lungs (Choi et al, 2008;Moral-Sanz et al, 2012). MPO, which is expressed abundantly in neutrophils, is a basic heme protein that utilizes chloride as a substrate and hydrogen peroxide as a co-substrate to generate ROS and free radical species that oxidatively modify lipids and proteins (Nauseef, 1986;Nauseef & Malech, 1986).…”
Section: Discussionmentioning
confidence: 99%